When complexity produces brutality - Sassen, Saskia (Sens public)

(untitled) (Département des littératures de langue française, 2010)
In a tentative project to understand how its own creativity led the advanced capitalism to the subprime crisis in the U. S., Saskia Sassen dicovers a secret link between high finance and an essentially formal approach of territorial realities. Where the average human being considers the earth worth to be valuated in itself as the basis for any human life, and any people as being entitled to be protected from misery by the resource they can flow into the social system, it suddenly appears that the financial techniques, such as the LBOS's are not restricted to corporate assets. Hence a comparison between what is actually occuring in most of the Global South countries, which are not only exporting their natural resources but selling their territories to foreign companies, and what happened with the subprime mortgage system. In both cases, the advanced capitalism created "surplus populations" effectively excluded from their own villages or houses. It becomes impossible for most of the people in the South to develop their own products. And in the Global North, a vast number of people were captured by distorted mortgage techniques, and left apart without any possibility to get what money they have spent into the system back. What is next?